2000
DOI: 10.4102/sajcd.v47i1.222
|View full text |Cite
|
Sign up to set email alerts
|

Use of the CID W22 as a South African English speech discrimination test

Abstract: South Africa currently lacks a pre-recorded South African English (SAE) specific speech discrimination test. In the absence of such a test, the SAE speaker recording (Tygerberg recording) of the American (USA) English (AE) CID W22 wordlists - in combination with the original American CID W22 normative data - is the most widely used alternative. The reliability and validity of this method, however, has never been formally assessed. This study assessed the performance of 15 normal hearing, female, first language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…First, recordings should use native talkers who exhibit a standard dialect of the target language (Weisleder & Hodgson, 1989). Evaluation of speech discrimination using recordings in a non-native dialect may significantly reduce performance, especially at presentation levels B/50 dB SPL (Wilson & Moodley, 2000). Second, words selected for the study should be familiar to the listeners, yet moderately difficult to identify (Campbell, 1965;Zakrzewski et al, 1976;Comstock & Martin, 1984;Weisleder & Hodgson, 1989).…”
Section: Sumariomentioning
confidence: 99%
“…First, recordings should use native talkers who exhibit a standard dialect of the target language (Weisleder & Hodgson, 1989). Evaluation of speech discrimination using recordings in a non-native dialect may significantly reduce performance, especially at presentation levels B/50 dB SPL (Wilson & Moodley, 2000). Second, words selected for the study should be familiar to the listeners, yet moderately difficult to identify (Campbell, 1965;Zakrzewski et al, 1976;Comstock & Martin, 1984;Weisleder & Hodgson, 1989).…”
Section: Sumariomentioning
confidence: 99%
“…On the potential for using non-South African language speech audiometry tests on South African populations, research has suggested that first-language speakers of South African English with normal hearing thresholds perform well on non-South African English speech recognition tests at suprathreshold levels but perform poorly at threshold levels. This was seen in studies using the National Acoustic Laboratories Arthur Boothroyd (NAL-AB) wordlists in Australian English (Wilson, Jones, & Fridjhon, 1998 ) and the Central Institute of the Deaf Wordlist 22 (CID W22) in American English (Wilson & Moodley, 2000 ). While not addressing SRT testing directly, these studies argue against using or adapting non-South African language speech audiometry tests for South African populations.…”
Section: Introductionmentioning
confidence: 93%
“…Although the listeners reported the talker recordings to be clearly intelligible, listeners from Spanish-language regions other than Mexico recognized low-intensity words with less accuracy. Thus, evaluation of word recognition using recordings in a nonnative accent may significantly reduce performance, especially at presentation levels B/50 dB SPL (Wilson & Moodley, 2000). Second, words selected for speech audiometry testing should be familiar to the listeners, yet moderately difficult to identify (Zakrzewski et al, 1976;Comstock & Martin, 1984;Weisleder & Hodgson, 1989).…”
Section: Sumariomentioning
confidence: 99%